On a problem of restoration of curves - Ligun, A. A.; Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the problem of asymptotically optimal placement of disks of the same radius under the condition of minimization of the Hausdorff distance between a given curve Γ and the union of disks under study.